Mexican school students’ perceptions of inclusion: A brief report on students’ social inclusion, emotional well-being, and academic self-concept at school - Pozas, Marcela; Trujillo, Claudia Jaquelina González; Letzel-Alt, Verena (Frontiers in Education, 2023)
With the increasing student diversity, inclusive education has only become more relevant. Given that inclusive education is considered as the most effective approach to improve quality of education and promote equity and social cohesion, research has focused on examining the facilitators and barriers of meaningful inclusive education as well as the effectiveness of inclusive education on students’ academic outcomes. In contrast, far less attention has been paid to explore students’ non-achievement outcomes, such as their socio-emotional development. Therefore, this brief report presents the results of a small-scale exploratory study which examines Mexican students’ perceptions regarding their social inclusion, school emotional well-being, and academic self-concept. A total of 101 Mexican students were included in the sample. Nonparametric tests such as Chi-Square goodness of fit, Mann-Whitney U and Dunn’s tests were conducted to analyze the data. Overall, results show that students in general perceive themselves included at school, however, students in attending private schools experience less school emotional well-being. Implications of the results as well as further lines of research are discussed.